Productivity, wages, and the returns to firm-provided training: fair shared capitalism? - Lopes, Ana Sofia (2019)
In this study, we develop an alternative modelling that examines a) the determinants of firm productivity and wages and b) the internal rate of return (IRR) to firm training for both firms and workers. Using a six-year linked employer-employee dataset, our estimates indicate that an additional hour of training per worker results in an increase of 0.12% in productivity and 0.04% in wages, or an increase of 0.16% and 0.08%, respectively, if one uses firm training as a stock variable. We then find that 82% of the gains in productivity are captured by firms and 18% by workers. Given the training costs, we finally obtain an IRR of 13% for firms and 33% for workers at sample means. Firms are heterogeneous, and we do find that dispersion in the rates of return across firms is high.